Design Principles for a Crowd-Based Prototype Validation Platform - Gottschalk, Sebastian; Aziz, Muhammad Suffyan; Yigitbas, Enes; Engels, Gregor (Software Business - 12th International Conference, ICSOB 2021, Drammen, Norway, December 2-3, 2021, Proceedings)

LLC Converter in Capacitive Operation Utilizing ZCS for IGBTs – Theory, Concept and Verification of a 2 kW DC-DC Converter for EVs - Urbaneck, Daniel; Rehlaender, Philipp; Böcker, Joachim; Schafmeister, Frank (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
LLC resonant converters typically employ power MOSFETs in their inverter stage. The generally weak reverse recovery behaviour of the intrinsic body diodes of those MOSFETs causes significant turn-on losses when being forced to hard commutations. Continuous operation in this way will lead to self-destruction of the transistors. Consequently, zero-voltage switching (ZVS) is essential in a MOSFET-based inverter stage. To ensure ZVS, the LLC converter is operated in the inductive region. On the contrary, IGBTs show dominant turn-off losses and are therefore conventionally not applied in LLC converters typically requiring high switching frequencies to achieve low output voltages. However, if the LLC converter is intentionally designed for capacitive operation, zero-current switching (ZCS) is enabled and thus robust and cost-efficient IGBTs can be applied in the inverter stage. The aim of this work is to investigate the use IGBTs in the inverter of an LLC converter. The theory behind the capacitive operated LLC is derived using a switched simulation model and compared with the fundamental harmonic approximation (FHA). The results prove FHA to be useless for practical converter design. Instead, a stress value analysis based on switched model simulations is proposed to the design a capacitive operated LLC utilizing ZCS. A 2 kW prototype for on-board EV applications was built to verify the theory and design approach. The prototype confirms the derived theory and thus the deployment of IGBTs in the inverter stage of LLC resonant converters. Synchronous rectification turns out to require a specific control solution, but if given the resulting efficiency in the most critical operation point exceeds the value of a MOSFET-based (inductive operated) LLC-design of an identical application. Therefore, this concept should be further developed.

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.

Immersive augmented reality system for the training of pattern classification control with a myoelectric prosthesis - Boschmann, Alexander; Neuhaus, Dorothee; Vogt, Sarah; Kaltschmidt, Christian; Platzner, Marco; Dosen, Strahinja (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Hand amputation can have a truly debilitating impact on the life of the affected person. A multifunctional myoelectric prosthesis controlled using pattern classification can be used to restore some of the lost motor abilities. However, learning to control an advanced prosthesis can be a challenging task, but virtual and augmented reality (AR) provide means to create an engaging and motivating training. Methods In this study, we present a novel training framework that integrates virtual elements within a real scene (AR) while allowing the view from the first-person perspective. The framework was evaluated in 13 able-bodied subjects and a limb-deficient person divided into intervention (IG) and control (CG) groups. The IG received training by performing simulated clothespin task and both groups conducted a pre- and posttest with a real prosthesis. When training with the AR, the subjects received visual feedback on the generated grasping force. The main outcome measure was the number of pins that were successfully transferred within 20 min (task duration), while the number of dropped and broken pins were also registered. The participants were asked to score the difficulty of the real task (posttest), fun-factor and motivation, as well as the utility of the feedback. Results The performance (median/interquartile range) consistently increased during the training sessions (4/3 to 22/4). While the results were similar for the two groups in the pretest, the performance improved in the posttest only in IG. In addition, the subjects in IG transferred significantly more pins (28/10.5 versus 14.5/11), and dropped (1/2.5 versus 3.5/2) and broke (5/3.8 versus 14.5/9) significantly fewer pins in the posttest compared to CG. The participants in IG assigned (mean ± std) significantly lower scores to the difficulty compared to CG (5.2 ± 1.9 versus 7.1 ± 0.9), and they highly rated the fun factor (8.7 ± 1.3) and usefulness of feedback (8.5 ± 1.7). Conclusion The results demonstrated that the proposed AR system allows for the transfer of skills from the simulated to the real task while providing a positive user experience. The present study demonstrates the effectiveness and flexibility of the proposed AR framework. Importantly, the developed system is open source and available for download and further development.
Keywords: Health Informatics; Rehabilitation

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Die Sterne sind für alle da - Eine empirische Untersuchung zu Anforderungen der Gestaltung von barrierefreien Online-Bewertungssystemen - Ahmeckovic, Emina

Wer schreibt der bleibt – Eine quantitative Untersuchung der Kundenbeziehung in Brand Communities und Smart Service Systems - Funk, Daniel

Wechselwirkungen von Hemmnissen und Motivatoren mit Blick auf die Abgabe von Online-Bewertungen - Rümpker, Till

Mitten ins Herz – Eine semantische Analyse von Spendenkampagnen auf Crowdfunding Plattformen - Roslan, Jan-Philipp

Digitale Diskriminierung – Ein systematischer Literaturüberblick - Speer, Laura

Personality Matters – Ein systematischer Literaturüberblick zur Anpassung von Anwendungssystemen an die Nutzerpersönlichkeit - Lender, Leonie

Auswirkungen von Anreizsystemen zu nutzergenerierten Inhalten auf digitalen Märkten – Ein systematischer Literaturüberblick - Steierlein, Gergely

Auswirkungen von Aggregationsmetriken von Bewertungen auf digitalen Märkten – Ein systematischer Literaturüberblick - Mai, Thanh Quynh

Achterbahn der Gefühle – Eine semantische Analyse von Spendenkampagnen im zeitlichen Verlauf der Corona Pandemie - Grieger, Nicole

Worauf achten AirBnb Gäste? Eine semantische Analyse von Online-Bewertungen mittels Latent-Dirichlet-Allocation - Dierkes, Lukas

Innovation in Nutzerkommentaren – Eine Analyse am Beispiel einer Rezept-Plattform - Tiggemann, Benjamin

Determinants of Loyalty in Online Communities: A Systematic Literature Review - Schlesiger, Laura

Konkurrent oder Komplementär? Eine empirische Analyse über das Nutzerverhalten in Online-Communities in Folge einer Smart Product Innovation - Dierkes, Johannes

Raising Money for a Good Cause – An Econometric Analysis of Key Factors to Successful Personal and Charitable Crowdfunding Campaigns - Krüger, Noah